2020
DOI: 10.1002/srin.202000131
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Embrittlement Susceptibility of Gas Metal Arc Welded Joints from a High‐Strength Low‐Alloy Steel Grade S690QL

Abstract: Herein, the hydrogen embrittlement (HE) susceptibility of base material and gas metal arc welds from a high‐strength low‐alloy steel grade S690QL by slow strain rate test (SSRT) with in situ hydrogen charging is investigated. To investigate the influence of welding process parameters on the HE susceptibility of welded joints, gas metal arc welds in multilayer technique with two different heat inputs are conducted. The results reveal a considerable loss of fracture elongation for all hydrogen‐charged specimens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…[1,2] The use of HSLA steels in welded structures can significantly reduce the consumption of resources and production costs. [3] Many studies focused on the development of high-performance welding consumables, new welding processes and welding parameter adjustment in pursuit of optimal mechanical properties of HSLA welded joints. [4] Lan et al analyzed the influence of microstructure aspects on the impact toughness of weld metal (WM) and heat-affected zone (HAZ) with different heat inputs to optimize the welding system of HSLA welded joint.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1,2] The use of HSLA steels in welded structures can significantly reduce the consumption of resources and production costs. [3] Many studies focused on the development of high-performance welding consumables, new welding processes and welding parameter adjustment in pursuit of optimal mechanical properties of HSLA welded joints. [4] Lan et al analyzed the influence of microstructure aspects on the impact toughness of weld metal (WM) and heat-affected zone (HAZ) with different heat inputs to optimize the welding system of HSLA welded joint.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] Christ et al have found the hydrogen embrittlement susceptibility of gas metal arc welded joints from a HSLA steel grade S690QL. [ 3 ] Zhu et al have found that the microstructural variations along WM, HAZ, and BM caused galvanic corrosion in the welded sample. [ 9 ] Wint et al have investigated the corrosion behavior of a HSLA welded joint in 0.017 M NaCl solution.…”
Section: Introductionmentioning
confidence: 99%